AMMONIA REMOVAL BEHAVIOR IN THE DOWNFLOW HANGING SPONGE BIOREACTOR - Izarul Machdar (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
Ammonia removal behavior in the DHS has been studied extensively including apply a DO microelectrodes and a gold method of microbial identification, i.e. Fluorescence In Situ Hybridization (FISH) approach by means of 16S rRNA-targeted oligonucleotide probes. With the HRT of 2 h, the ammonia removal rate in the bioreactor was achieved 0,24 kgN.m-3.d-1, and nitrogen-losing rate was approximate 0,08 kgN.m-3.d-1. Moreover, the most important of this system is no requirement external aeration input. FISH of the DHS sludge revealed that nitrifiers could be detected with Nso190, NSR1156, or NIT3 probe, form dense clusters, and they mainly settled in the surface region of the heterotrophic aggregates. Ammonia oxidizers and nitrite oxidizers grown in DHS sludge in separated solitary occurrence. Nitrospira spp. were more likely responsible to oxidize of nitrite rather than Nitrobacter spp.